THE EFFECT OF PICTURE AND PICTURE LEARNING MODELS ASSISTED BY LEARNING VIDEO MEDIA ON THE LEARNING RESULTS OF CLASS III STUDENTS AT SDN BABADAN 1 PARON - Konikatul Rahmawati; Yes Matheos Lasarus Malaikosa; Budi Sasomo (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2023)
Learning models play an important role in the learning process and affect the results of the student learning process. Improvements to the learning process and the use of appropriate learning models will help improve student learning results. Learning models that can improve learning results, concentration, motivation and provide opportunities for students to be more active are picture and picture models assisted by learning video media. The purpose of this study was to determine the effect of picture and picture learning models assisted by learning video media on the learning resilts of the cognitive domain of class III students theme 6 Energy and Change. This research was conducted at SDN Babadan 1 Paron. This study used quantitative approach, PreExperimental method and OneGroup Pretest-Posttest design. The results showed that there was a significant influence on the use of picture and picture learning models assisted by video learning media on the cognitive learning outcomes of grade III students theme 6 Energy and its Changes subtheme 2 Energy Change at SDN Babadan 1 Paron. It is indicated by the value of Sig.(2-tailed) which is 0.000 which is smaller than 0.05 and it is known that the tcount > ttable is 4.755 > 2.074 (0.05/2). So the conclusion is that the picture and picture learning model assisted by learning video media is effective for use in the learning process in class III theme 6 Energy and its changes subtheme 2 Energy Change.